An unusual presentation of paediatric Listeria meningitis with selective spinal grey matter involvement and acute demyelinating polyneuropathy. (January 2016) - Papandreou, A.; Hedrera-Fernandez, A.; Kaliakatsos, M.; Chong, W.K.; Bhate, S.
Abstract: Background: Paediatric Listeria meningitis is rare, especially in immuno-competent children, but associated with significant mortality and morbidity and frequent complications. Methods: We report an unusual case of Listeria meningitis in a previously healthy 35 month-old girl with selective spinal grey matter involvement and demyelination in neurophysiological studies. Despite adequate antibiotic treatment, the case was initially complicated by ventriculitis, hydrocephalus and tonsillar herniation through the foramen magnum, requiring external ventricular drainage and subsequent ventriculoperitoneal shunt insertion. Paucity of movements, hypotonia, areflexia and bladder dysfunction then became evident. Results: Electromyogram and nerve conduction studies showed acute inflammatory demyelinating polyneuropathy and the patient received intravenous immunoglobulin followed by corticosteroids. MRI scans with contrast revealed extensive whole cord selective grey matter signal changes. She required extensive neurorehabilitation, making gradual (but incomplete) recovery. Conclusion: Spinal cord involvement is rare in neuro-listeriosis and there no previous paediatric reports of Listeria -related myelitis or demyelinating polyneuropathy. The mechanism behind these presentations is unclear but an auto-immune response to the infection might be considered. Highlights: Listeria meningitis is uncommon in paediatrics but associated with high rates of morbidity, mortality and complications. Increased clinical awareness, early instigation of appropriate treatment and monitoring for complications is paramount. This is the first paediatric case with whole cord grey matter involvement and acute inflammatory demyelinating polyneuropathy. The grey matter selectivity and nerve conduction findings suggest underlying autoimmune or parainfectious mechanisms.